From ICT to LKT: learning and knowledge technologies - Lozano, Roser (Anuario ThinkEPI, 2011)
Librarians and information scientists must seek collaboration with other professionals, not only -as until now- with the computer scientists, but also with teaching experts. In this sense they must talk less about information and communication technologies (ICT) and more about learning and knowledge technologies (LKT). Libraries (school, public, university) do not centralize the information flows anymore, so their work must now be more oriented to user education and training.
Keywords: Learning; Training; Education; Collaboration; Professionals; Libraries; Librarians.